Assessment of microplastics in Irish river sediment. Issue 7 (July 2022) - Murphy, Loriane; Germaine, Kieran; Kakouli-Duarte, Thomais; Cleary, John
Abstract: Microplastics (MPs) are environmental pollutants of growing concern, and awareness of MPs pollution in marine and freshwater environments has increased in recent years. However, knowledge of MPs contamination in riverine sediments in Ireland is limited. To address this, we collected and analysed sediment samples from 16 selected sites along the River Barrow. Microplastics were extracted through a density separation method, after which their size, colour, and shape were analysed under a stereo microscope (Optica SZM-2). Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy was used to identify polymer types. A total of 690 MPs were recovered from the 16 sites, with fibres as the dominant MP type. The highest concentration of MPs was 155 MP fibres kg −1 wet sediment found in samples collected from Graiguenamanagh, Co. Kilkenny (GK). The majority of the recovered MPs were polyethylene (PE), polypropylene (PP), nylon, and cellulose acetate (CA) fibres. Overall, this study highlighted the presence of MPs in Irish river sediments and provided a baseline for future studies on MPs pollution. Further research is needed to better understand sources, distribution, and effects of MPs in freshwater ecosystems. Graphical abstract: Image 1 Abstract : River sediments; MPs; Density separation; Quantification; Characterisation; ATR-FTIR.